CICATRICIAL ECTROPION REPAIR DUE TO TRAUMA : A CASE REPORT: Poster Presentation - Case Report - Resident - Rino Agustian Praja; Hendrianti; Mardijas Efendi (Majalah Oftalmologi Indonesia, 2023)
Introduction : Cicatricial ectropion is a complication that can occur after trauma. Scar tissue formation causes anterior lamellae shortening (skin and orbicularis muscle), resulting in outward lid margins rotation. Case Illustration : A 16 y.o male patient came with complaints of the left upper and lower eyelids folding outwards since 3 months ago after trauma, watery eye. Examination VOD 20/20, VOS 20/50. Scar on the superior and inferior lids, the inferior lid margin is folded out, inferior tarsal conjunctiva is visible, lagophthalmus 4 mm, fissure palpebral vertical (FPV) 12 mm, margin reflex distance (MRD) 1 = 4 mm, MRD2 = 8 mm, fissure palpebral horizontal (FPH) 30 mm, conjunctival injection. Corneal (macular) scars central-peripherally at 3-6 o'clock. Patient was diagnosed with cicatrical ectropion with left eye corneal scar and ectropion repair was performed with full-thickness skin graft from retroarticular. One week and six weeks after surgery, FPV improved to 10 mm, MRD1 = 4, MRD2 = 6 mm, FPH 30 mm, and lagophthalmos 2 mm became 1 mm. Discussion : Cicatricial ectropion is usually treated in 3 procedures: release vertical scar traction, horizontal lid tightening, repair anterior lamella can be done with full-thickness skin graft. horizontal lid tightening in this case not carried out because of no laxity. Conclusion : Scar traction release and repair anterior lamella with full-thickness skin graft from retroauricular was choice in this case because extensive defect and ectropion grade 3. After surgery anatomical structure of the lids and looks better aesthetically.